Autoimmune Lymphoproliferative Syndrome-FAS Patients Have an Abnormal Regulatory T Cell (Treg) Phenotype but Display Normal Natural Treg-Suppressive Function on T Cell Proliferation - Mazerolles, Fabienne; Stolzenberg, Marie-Claude; Pelle, Olivier; Picard, Capucine; Neven, Benedicte; Fischer, Alain; Magerus-Chatinet, Aude; Rieux-Laucat, Frederic (Frontiers in Immunology, 2018)
Objective: Autoimmune lymphoproliferative syndrome (ALPS) with FAS mutation (ALPS-FAS) is a non-malignant, non-infectious, lymphoproliferative disease with autoimmunity. Given the central role of natural regulatory T cells (nTregs) in the control of lymphoproliferation and autoimmunity, we assessed nTreg suppressive function in 16 patients with ALPS-FAS. Results: The proportion of CD25highCD127low Tregs was lower in ALPS-FAS patients than in healthy controls. This subset was correlated with reduced CD25 expression in CD3+CD4+ T cells from ALPS patients, and thus an abnormally low proportion of CD25highFOXP3+ Helios+ T cells. The ALPS patients also displayed a high proportion of naïve Treg (FOXP3lowCD45RA+) and an unusual subpopulation (CD4+CD127lowCD15s+CD45RA+). Despite this abnormal phenotype, the CD25highCD127low Tregs’ suppressive function was unaffected. Furthermore, conventional T cells from FAS-mutated patients showed normal levels of sensitivity to Treg suppression. Conclusion: An abnormal Treg phenotype is observed in circulating lymphocytes of ALPS patients. However, these Tregs displayed a normal suppressive function on T effector proliferation in vitro. This is suggesting that lymphoproliferation observed in ALPS patients does not result from Tregs functional defect or Teffector cells insensitivity to Tregs suppression.